Security Analysis in Wireless Sensor Networks - Murat Dener (International Journal of Distributed Sensor Networks)
In recent years, wireless sensor network (WSN) is employed in many application areas such as monitoring, tracking, and controlling. For many applications of WSN, security is an important requirement. However, security solutions in WSN differ from traditional networks due to resource limitation and computational constraints. This paper analyzes security solutions: TinySec, IEEE 802.15.4, SPINS, MiniSEC, LSec, LLSP, LISA, and LISP in WSN. The paper also presents characteristics, security requirements, attacks, encryption algorithms, and operation modes. This paper is considered to be useful for security designers in WSNs.